Health Outcomes and Economic Growth Nexus: Evidence from Nigeria - Modibbo, Haruna; Inuwa, Nasiru (Journal of Business and Economic Options, 2020)
This paper examines the intricate relationship between health outcomes and economic growth in Nigeria, aiming to shed light on the long-term dynamics between these two vital domains. Through empirical analysis, our study uncovers a compelling long-run association between health outcomes and economic growth in Nigeria. Our findings reveal that both life expectancy and crude death rate, serving as key indicators of health, exhibit a significant long-run negative impact on economic growth over the study period. This suggests that improvements in health outcomes, as measured by increased life expectancy and reduced crude death rates, are conducive to fostering economic growth within the Nigerian context. Furthermore, our analysis employs Granger causality tests to explore the directionality of the relationship between health outcomes and economic growth. The results reveal a unidirectional causality, indicating that changes in life expectancy and crude death rate precede and influence economic growth in Nigeria. Based on these empirical findings, our study underscores the importance of prioritizing investments in healthcare and public health initiatives as a means to bolster overall economic development. We advocate for government interventions at various levels to create conducive conditions for enhancing health outcomes in Nigeria, thereby fostering a healthier population and stimulating sustainable economic growth. Thus, research underscores the imperative for policymakers to recognize the intrinsic linkages between health and economic prosperity, emphasizing the need for concerted efforts to improve healthcare infrastructure and promote public health initiatives as integral components of Nigeria's development agenda.